DETERMINING THE TANNIN CONTENT IN PISANG AMBON (Musa × paradisiaca L.) WITH THE POTENTIAL AS ANTHELMINTIC - Dwi Haryatmi; Indah Tri Susilowati (Jurnal Kimia Riset, 2022)
Tannins result from plants' secondary metabolism, closely associated with plant defense mechanisms against insects. Condensed tannins can disrupt the life cycle of parasitic nematodes starting from eggs, adult worms, and larvae. Currently, the antiparasitic properties of condensed tannins are being investigated as an alternative for controlling parasites. The people use the young Pisang Ambon (Musa × parasidiaca L.) as an anthelmintic. People generally use this part of the banana peel. Based on this, a study was conducted to determine the tannin content in the peel and fruit of Pisang Ambon (Musa × parasidiaca L.). The research was conducted by extracting the fruit and peel of young Pisang Ambon by maceration method using 96% ethanol as solvent. The Harborne method and Thin Layer Chromatography tested the presence of secondary metabolites. The tannin content was determined by the visible, ultraviolet spectrophotometric method. The qualitative results showed that the peel and fruit of Pisang Ambon contained condensed tannins. Meanwhile, the quantitative results showed that the tannin content of the fruit (54.98% w/w) was higher than the peel (14.32 %w/w).